Retrocaval ureter: an unsual cause of hydronephrosis in an adult - Hassan, Radhiana; Che Mohamed, Siti Kamariah; Kamarulzaman, Mohd Nazli (2010)
Retrocaval ureter is a rare congenital anomaly. We describe a case of right upper tract collecting system dilatation caused by a retrocaval ureter in an adult patient. Conflicting initial radiological findings had misled the surgeons in managing this patient. This case illustrates the importance of an accurate radiological diagnosis of this condition prior to any surgical intervention for an appropriate and successful surgical management.